PEMBELAJARAN VOKAL DI SANGGAR BINA VOKALIA HARMONIA KOTA PONTIANAK - Sufriyanti, Mita; Sanulita, Henny; Munir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted to know learning process and learning achievement at Sanggar Bina Vokalia Harmonia, Pontianak. Sanggar Bina Vokalia Harmonia is the first vocal course in Pontianak. This research was designed as a qualitative study by using descriptive method. The data were then analyzed by using reduction of research data about vocal learning at Sanggar Bina Vokalia Harmonia which described the data that have been reduced in to narrative text and concluded the results of research to obtain a description of process and learning achievement at Sanggar Bina Vokalia Harmonia. Results of the research showed that there are four stages of learning which covers vocal warms up, vocal exercises, voice deepening and singing songs. Learning outcomes obtained by learners can be said good, because the majority of learners have experienced changes in knowledge, skills and vocal skills in accordance with the results of observations, interviews and questionnaires.Â Keyword: Learning, Vocal, Sanggar